(untitled) - Phelan, Susan E. (Chicago, 1992)
This manual provides detailed, step-by-step instruction in basic phlebotomy techniques. From routine procedures to patient interaction skills, it incorporates various exercises to assist students in learning these techniques. Procedures covered include venipuncture, skin punctures, modified Ivy bleeding times, blood smears, blood cultures, and glucose tolerance testing. Safety, quality assurance/quality control and professionalism are also discussed. New information and techniques are introduced in a stepwise process that gradually acclimatizes the learner to phlebotomy practice. The workbook is designed to enable students to master standard phlebotomy procedures and to enter the clinical setting easily and effectively, requiring minimal instruction.
Keywords: Kĩ thuật tháo ống máu,Phlebotomy